Molecular γ-amino butyric acid and its crystals: Structural, electronic and optical properties (2023)
This work presents the formation of monoclinic γ-aminobutyric acid (GABA) crystals grown from an aqueous ethanol solution with the dimensions 4 ​× ​1 ​× ​0.6 ​mm3. The structural properties of the grown crystal were evaluated via X-ray diffraction analysis of the powder and single crystal, which confirmed a monoclinic crystal system with space group P21/c. Thermal stability and the melting point of the synthesized GABA crystal were investigated using TG-DSC measurements. We also characterized experimentally monoclinic and molecular GABA solvated in water, obtaining its optical absorption spectrum in the UV-VIS region. Time-dependent DFT calculations were performed for the GABA molecule in the neutral and zwitterion forms to understand their optical absorption features. Structural, electronic, and optical properties of four γ-aminobutyric acid (GABA) crystal polymorphs (monoclinic, tetragonal, hexagonal, and monohydrate) were achieved through DFT calculations employing a dispersion corrected exchange-correlation functional. Differences in the electronic and optical properties between polymorphs are discussed. We predict the GABA monoclinic crystal to be an indirect gap semiconductor with a gap value of 5.02 ​eV, in good agreement with our experimental measurements. Considering the other three polymorphs, their fundamental gap values range from 4.6 ​eV to 5.16 ​eV (being direct for all of them, except the monohydrate). The absorption spectra calculations reveal a significant optical anisotropy for all GABA crystals, with the highest optical absorption for the monoclinic structure in the 5–6 ​eV energy range